Design de objetos de aprendizagem digital do ponto de vista da usabilidade - Mochiuti, Gustavo Henrique; Valente, Vania Cristina Pires Nogueira [UNESP] (Science and Education Research Council (COPEC), 2014)
Technological resources and the media are contributing to socioeconomic development, including the education sector. Application of Digital Learning Objects support learning, serving as a tool for distance learning arrangements and classroom. The quality of design in instructional materials is one factor that implies the motivation of students and support their learning, within this context, the creation of educational interactive multimedia applications should excel the content and good usability, while facilitating user interaction. The aim of this paper was to establish parameters for the creation and management of Digital Learning Objects.
Keywords: Index Terms|Digital Learning Objects|Interactivity; Usability